The Emerald handbook of women and entrepreneurship in developing economies - Rezaei, Shahamak (Emerald Publishing Limited, 2021)
The Emerald Handbook of Women and Entrepreneurship in Developing Economies examines women's role in entrepreneurial practices in a range of developing countries and applies unique strategic contextual frameworks to analyse, interpret and understand individual processes, themes and issues. This book brings together a truly global range of scholarly voices to examine women and entrepreneurship in developing nations, exploring their practices and motivations in relation to individual, societal and institutional factors, with gender roles, role models and entrepreneurial ecosystems among the many issues interrogated. This ambitious collection presents an illuminating and ground breaking analysis of opportunities, innovations, issues and structural limits across countries which are underrepresented in the available literature to date and will be enlightening reading for all those interested in new entrepreneurial theory and practice.